Skeletal evidence of tuberculosis in a modern identified human skeletal collection (Certosa cemetery, Bologna, Italy). Issue 3 (24th February 2015) - Mariotti, Valentina; Zuppello, Micol; Pedrosi, Maria Elena; Bettuzzi, Matteo; Brancaccio, Rosa; Peccenini, Eva; Morigi, Maria Pia; Belcastro, Maria Giovanna
ABSTRACT The diagnosis of tuberculosis (TB) in osteoarcheological series relies on the identification of osseous lesions caused by the disease. The study of identified skeletal collections provides the opportunity to investigate the distribution of skeletal lesions in relation to this disease. The aim of this study was to examine the skeletal evidence for TB in late adolescent and adult individuals from the identified human collection of the Certosa cemetery of Bologna (Italy, 19th–20th c.). The sample group consists of 244 individuals (138 males, 106 females) ranging from 17 to 88 years of age. The sample was divided into three groups on the basis of the recorded cause of death: TB (N = 64), pulmonary non‐TB (N = 29), and other diseases (N = 151). Skeletal lesions reported to be related to TB were analyzed. The vertebral lesions were classified into three types: enlarged foramina (EnF, vascular foramina with diameter of 3–5 mm), erosions (ER), and other foramina (OtF, cavities of various shapes > 3 mm). A CT scan analysis was also performed on vertebral bodies. Some lesions were seldom present in our sample (e.g., tuberculous arthritis). OtF (23.7%) and subperiosteal new bone formation on ribs (54.2%) are significantly more frequent in the TB group with respect to the other groups. The CT scan analysis showed that the vertebrae of individuals who have died of TB may have internal cavities in the absence of external lesions. These traits represent useful elements in the paleopathological diagnosis of TB. Am J Phys Anthropol 157:389–401, 2015. © 2015 Wiley Periodicals, Inc.